Answer:
43.60
Step-by-step explanation:
12.36+31.24
Simplify: |3 – 10| - (12 / 4 + 2)^2
Answer:
-18
Step-by-step explanation:
= |3 – 10| - (12 / 4 + 2)^2
= 7 - (3 + 2)^2
= 7 - (5)^2
= 7 - 25
= -18
Find the midpoint of the line segment with the given endpoints
(10,2) and (8,4)
Answer:
The midpoint of the line segment is (9,3).
Step-by-step explanation:
To find the midpoint of a line segment, we use the midpoint formula, ( (x1 + x2)/2, (y1+y2)/2). This means that to find the midpoint, we must add together both of the x-values of the endpoints and divide by 2 and do the same with the y values, basically finding the average of the two endpoints, or the middle.
x1 + x2 = 10 + 8 = 18
18/2 = 9
y1 + y2 = 2 + 4 = 6
6/2 = 3
Therefore, the midpoint of the line segment is (9,3).
Hope this helps!
The function p(x) = -2(x-9)2 + 100 used to determine the profit on T-shirts sold for x dollars. What would the profit from sales be if the price of T-shirts were 15 apiece
Answer:
$28.
Step-by-step explanation:
p(x) = -2(x - 9)^2 + 100
If the prices (x) = 15 dollars we work out the profit by substituting x = 15 in the above formula:
p(15) = -2(15 - 9)^2 + 100
= -2 * 6^2 + 100
= $28.
Answer:
28
Step-by-step explanation:
What is the volume of the composite figure?
A. 140 cubic inches
B. 147 cubic inches
C. 168 cubic inches
D. 196 cubic inches
Answer:
A. 140 cubic inches
Step-by-step explanation:
The total volume is the volume of the rectangular prism at the bottom plus the volume of the pyramid on top.
The volume of the prism is width times length times height.
V = wlh
V = (3)(7)(4)
V = 84
The volume of the pyramid is one third the area of the base times the height.
V = ⅓ Ah
The base of the pyramid is a rectangle. Its area is the width times length. The height of the pyramid is the total height minus the height of the prism.
V = ⅓ (3)(7)(12−4)
V = 56
So the total volume is:
V = 84 + 56
V = 140
Answer:
140 cubic inches
Step-by-step explanation:
The figure is a regular hexagon with side length 26 ft.
What is the length of y?
Answer: the length is 13
Step-by-step explanation:
one side is 26 ft. and y is half of one side so by dividing 26 by 2 you would get 13
john is five years older than his sister. the product of their present ages is 150.
John's present age is (blank) years, and this sister's present age is (blank) years
so i believe you have to answer this with the quadratic formula but I'm not sure. please help
John's present age is 15 years, and his sister's present age is 10 years.
We have,
Let's denote John's sister's age as x.
According to the given information,
John is five years older than his sister, so John's age would be x + 5.
The product of their present ages is 150, which means:
x * (x + 5) = 150
Expanding the equation:
x² + 5x = 150
Rearranging the equation to standard quadratic form:
x² + 5x - 150 = 0
Now we can solve this quadratic equation.
Factoring or using the quadratic formula will give us the values of x, representing the sister's age.
Factoring the equation:
(x - 10)(x + 15) = 0
Setting each factor to zero:
x - 10 = 0 or x + 15 = 0
Solving for x:
x = 10 or x = -15
Since ages cannot be negative, we can discard the solution x = -15. Therefore, the sister's present age is x = 10.
John's present age is then calculated by adding 5 years to his sister's age:
John's age = x + 5 = 10 + 5 = 15 years.
Thus,
John's present age is 15 years, and his sister's present age is 10 years.
Learn more about expressions here:
https://brainly.com/question/3118662
#SPJ2
By forming a quadratic equation from the given problem, we determine that John's present age is 15 years and his sister's present age is 10 years.
Let's designate John's age as J and his sister's age as S. We've been given two pieces of information: John is five years older than his sister, and the product of their present ages is 150. Mathematically, these can be expressed as:
J = S + 5J * S = 150Substituting the first equation into the second gives us:
(S + 5) * S = 150
Expanding and rearranging, we get a quadratic equation:
S2 + 5S - 150 = 0
To solve for S, we can either factor the quadratic equation or use the quadratic formula. Factoring seems simpler in this case:
(S + 15)(S - 10) = 0
This gives us two possible values for S: -15 and 10. Since ages cannot be negative, we discard S = -15 and keep S = 10. Now we can find John's age:
J = S + 5 = 10 + 5 = 15
Therefore, John's present age is 15 years, and his sister's present age is 10 years.
Triangles are congruent if they have the same ____.
Answer:
D. size and shape
Step-by-step explanation:
Triangles are congruent if they have the same size and shape.
Write the product in its simplest form
-3y.3y4
Enter the correct answer.
Answer:
[tex]\large\boxed{-9y^5}[/tex]
Step-by-step explanation:
[tex]-3y\cdot3y^4=(-3\cdot3)(y\cdot y^4)\qquad\text{use}\ a^n\cdot a^m=a^{n+m}\\\\=-9y^{1+4}=-9y^5[/tex]
Suppose that the time it takes to do a job is inversely proportional to the number of workers. That is, the more workers on the job the less time required to complete the job. If it takes 3 workers 16 days to finish a job, how long will it take 8 workers
Answer: 6 days.
Step-by-step explanation:
Inverse proportion equation has the form:
[tex]y=\frac{k}{x}[/tex]
Where "k" is the constant of proportionality.
Let be "y" the time it takes to do a job (number of days) and "x" the number of workers.
We can find "k" knowing that it takes 3 workers 16 days to finish a job:
[tex]16=\frac{k}{3}\\\\k=16*3\\\\k=48[/tex]
To find how long will it take 8 workers to finish the job, you must substitute the value of "k" and [tex]x=8[/tex] into [tex]y=\frac{k}{x}[/tex]. Then you get:
[tex]y=\frac{48}{8}\\\\y=6[/tex]
Let f(x)=2^x and g(x)=x-2. The graph of (f o g)(c) is shown below. What is the domain of (f o g)(x)?
The domain of the outer function is all real numbers, because f(x) is an exponential function.
The domain and range of g(x) are all real numbers.
So, the domain of the composition is again all real numbers, because there is no way that an output from g(x) will not be a valid input for f(x).
For this case we have the following functions:
[tex]f (x) = 2 ^ x\\g (x) = x-2[/tex]
We must find [tex](f_ {o} g) (x):[/tex]
By definition we have to:
[tex](f_ {o} g) (x) = f [g (x)][/tex]
So:
[tex](f_ {o} g) (x) = 2 ^ {x-2}[/tex]
By definition, the domain of a function is given by all the values for which the function is defined. Thus, the domain of the composite function is:
In this case, there are no real numbers that make the expression indefinite.
Thus, the domain is given by all the real numbers.
Answer:
All the real numbers
Select the correct answer from each drop-down menu.
Ashley has 500 songs in his music player. Every week he adds 10 songs to his collection. How many songs will he have in his music player after
20 weeks?
The output of the function (f(n)=500+10n) or (f(n)=10+20n).the output of the function is (700/600)
when the input is 20
Answer:
700
Step-by-step explanation:
he originally has 500 songs which is the constant. He adds 10 songs a week which is the slope. and 20 will be the number of weeks. You can make the equation y=10x+500 and replace the x with 20. 20 times 10 is 200 and 200 plus 500 is 700 which is your answer
where d is the length of the diameter. If d is a rational number, what can you conclude about the circumference?
Answer:
The circumference is a irrational number
Step-by-step explanation:
we know that
The circumference of a circle is equal to
[tex]C=\pi D[/tex]
where
D is the diameter
In this problem we have that
[tex]D=d\ units[/tex] ---> is a rational number
substitute
[tex]C=\pi (d)[/tex]
[tex]C=d\pi\ units[/tex]
Remember that
The number π is a irrational number
and
If you multiply a rational number by a irrational number, the result is a irrational number
therefore
The circumference is a irrational number
Write a polynomial function of least degree with integral coefficients that has the given zeros. –2, –3,3 – 6i
Answer:
f(x) = (x+2)(x+3)(x-(3-6i))(x-(3+6i))
f(x) = 270 + 189 x + 21 x^2 - x^3 + x^4
Step-by-step explanation:
First of all, we must know that complex roots come in conjugate pairs.
So the zeros of your equation would be
x = -2
x = -3
x = 3 - 6i
x = 3 + 6i
Your polynomial is of fourth degree.
f(x) = (x-(-2))(x-(-3))(x-(3-6i))(x-(3+6i))
f(x) = (x+2)(x+3)(x-(3-6i))(x-(3+6i))
Please , see attached image below for full expression
f(x) = 270 + 189 x + 21 x^2 - x^3 + x^4
Answer:
The required polynomial is [tex]P(x)=a\left(x^4-x^3+21x^2+189x+270\right)[/tex].
Step-by-step explanation:
The general form of a polynomial is
[tex]P(x)=a(x-c_1)^{m_1}(x-c_2)^{m_2}...(x-c_n)^{m_n}[/tex]
where, a is a constant, [tex]c_1,c_2,..c_n[/tex] are zeroes with multiplicity [tex]m_1,m_2,..m_n[/tex] respectively.
It is given that –2, –3,3 – 6i are three zeroes of a polynomial.
According to complex conjugate root theorem, if a+ib is a zero of a polynomial, then a-ib is also the zero of that polynomial.
3 – 6i is a zero. By using complex conjugate root theorem 3+6i is also a zero.
The required polynomial is
[tex]P(x)=a(x-(-2))(x-(-3))(x-(3-6i))(x-(3+6i))[/tex]
[tex]P(x)=a(x+2)(x+3)(x-3+6i)(x-3-6i)[/tex]
[tex]P(x)=a\left(x^2+5x+6\right)\left(x-3+6i\right)\left(x-3-6i\right)[/tex]
On further simplification, we get
[tex]P(x)=a\left(x^3+6ix^2+2x^2+30ix-9x+36i-18\right)\left(x-3-6i\right)[/tex]
[tex]P(x)=a\left(x^4-x^3+21x^2+189x+270\right)[/tex]
Therefore the required polynomial is [tex]P(x)=a\left(x^4-x^3+21x^2+189x+270\right)[/tex].
What is the product of eight factors of 10^4
Answer:
2ε + 12 [two trillion (twelve zeros)]
Step-by-step explanation:
[1][2][4][5][10][1000][2000][2500] (1 is unnecessary)
If you are talking about the FIRST 8 factors of 10000 [10⁴], then here you are. Multiply all those numbers to get the calculator notation answer above, or two trillion.
**This question is not specific enough, which was why I improvised and thought that this was what you meant. I apologize if this was not what you meant and I also hope this was what you were looking for.
I am joyous to assist you anytime.
Answer:
[tex]10^{32}[/tex].
Step-by-step explanation:
eight factors of 10^4 are
[tex]10^4*10^4*10^4*10^4*10^4*10^4*10^4*10^4 = (10^4)^8 = 10^{4*8}=10^{32}[/tex]
that is one hundred nonillion.
Which functions have an additive rate of change of 3? Select TWO options
Answer:
Second table.
Step-by-step explanation:
A function has an additive rate of change if there is a constant difference between any two consecutive input and output values.
The additive rate of change is determined using the slope formula,
[tex]m = \frac{y_2-y_1}{x_2-x_1} [/tex]
From the first table we can observe a constant difference of -6 among the y-values and a constant difference of 2 among the x-values.
[tex]m = \frac{ - 9- - 3}{4-2} = - 3[/tex]
For the second table there is a constant difference of 3 among the y-values and a constant difference of 1 among the x-values.
The additive rate of change of this table is
[tex]m = \frac{ - 1 - - 4}{3 - 1} = 3[/tex]
Therefore the second table has an additive rate of change of 3.
Answer: it’s A and E
First and last one
Step-by-step explanation:
Find the quadratic function that fits the following data. which one function fits.
Answer:
C
Step-by-step explanation:
The general rule for the quadratic function is
[tex]y=ax^2+bx+c[/tex]
Use the data from the table:
[tex]y(50)=130\Rightarrow 130=a\cdot 50^2+b\cdot 50+c\\ \\y(70)=130\Rightarrow 130=a\cdot 70^2+b\cdot 70+c\\ \\y(90)=200\Rightarrow 200=a\cdot 90^2+b\cdot 90+c[/tex]
We get the system of three equations:
[tex]\left\{\begin{array}{l}2500a+50b+c=130\\ \\4900a+70b+c=130\\ \\8100a+90b+c=200\end{array}\right.[/tex]
Subtract these equations:
[tex]\left\{\begin{array}{l}4900a+70b+c-2500a-50b-c=130-130\\ \\8100a+90b+c-2500a-50b-c=200-130\end{array}\right.\Rightarrow \left\{\begin{array}{l}2400a+20b=0\\ \\5600a+40b=70\end{array}\right.[/tex]
From the first equation
[tex]b=-120a[/tex]
Substitute it into the second equation:
[tex]5600a+40\cdot (-120a)=70\Rightarrow 800a=70,\\ \\ a=\dfrac{7}{80},\\ \\ b=-120\cdot \dfrac{7}{80}=-\dfrac{21}{2}=-10.5[/tex]
So,
[tex]2500\cdot \dfrac{7}{80}+50\cdot (-10.5)+c=130\Rightarrow 218.75-525+c=130\\ \\c=130-218.75+525=436.25[/tex]
The quadratic function is
[tex]y=\dfrac{7}{80}x^2-10.5x+436.25\\ \\y=0.0875x^2-10.5x+436.25[/tex]
This graph represents the function f(x) = x^2 - 4x + 3/ x^2 + ax + b. a= ___ b= ___
Answer:
f(x) = (x+2)(x-8)/(x-6)(x+4) <-> x=6,x=-4
i(x) = (x-4)(x-6)/(x-2)(x+8) <-> x=2,x=-8
k(x) = (x-2)(x+8)/(x+6)(x-4) <-> x=-6,x=4
m(x) = (x+4)(x-6)/(x+2)(x-8) <-> x=-2,x=8
Step-by-step explanation:
The function is discontinuous if the denominator is zero.
We will check for which function the values are given
1) f(x) = (x+2)(x-8)/(x-6)(x+4)
if x = 6 and x = -4 the denominator is zero
So, x=6 and x=-4 given
2) g(x) = (x+4)(x-8)/(x+2)(x-6)
if x = -2 and x = 6 the denominator is zero
So, x= -2 and x= 6 not given so, g(x) will not be considered
3) h(x)= (x+2)(x-6)/(x-8)(x+4)
if x = 8 and x = -4 the denominator is zero
So, x= 8 and x= -4 not given so, h(x) will not be considered
4) i(x) = (x-4)(x-6)/(x-2)(x+8)
if x = 2 and x = -8 the denominator is zero
So, x= 2 and x= -8 given
5) j(x) = (x-2)(x+6)/(x-4)(x+8)
if x = 4 and x = -8 the denominator is zero
So, x= 4 and x= -8 not given so, j(x) will not be considered
6) k(x) = (x-2)(x+8)/(x+6)(x-4)
if x = -6 and x = 4 the denominator is zero
So, x= -6 and x= 4 given
7) l(x) = (x-4)(x+8)/(x+6)(x-2)
if x = -6 and x = 2 the denominator is zero
So, x= -6 and x= 2 not given so, l(x) will not be considered
8) m(x) = (x+4)(x-6)/(x+2)(x-8)
if x = -2 and x = 8 the denominator is zero
So, x= -2 and x= 8 given
seven sixteeths wrote as a decimal
Answer:
The answer is 0.4375 .
Hope this helps!
y= 3x2 + 6x + 1
What’s the answer
Answer
Y= 3 × 2 + 6x + 1 = 6 + 6x +1 = 6x + (6+1) = 6x + 7
Answer:
This is a function, so the answer is a plot, you can see it in the attached picture
Step-by-step explanation:
This is a function, the best way to go here is to graph.
First lest find the roots of 3x2+6x+1, you do this by using the quadratic equation
[tex]x_{1} = \frac{-b + \sqrt{b^{2}-4ac }}{2a}\\x_{2} = \frac{-b - \sqrt{b^{2}-4ac }}{2a}[/tex]
Where a=3, b=6, c=1
Using that, you get, x1 = -1 - sqrt(2/3) which is a negative number, and x2=sqrt(2/3) - 1 which is a negative number.
These number represent values that makes the function equals =0
Now if we make x=0, the result is y=1,
We have a better idea of what is to plot and it is shown on the attached picture
If 5+ 20 -22-3х - 10.2-2x+5, what is the value of х?
Answer:
3Step-by-step explanation:
[tex]5+20\cdot2^{2-3x}=10\cdot2^{-2x}+5\qquad\text{subtract 5 from both sides}\\\\20\cdot2^{2-3x}=10\cdot2^{-2x}\qquad\text{divide both sides by 10}\\\\2\cdot2^{2-3x}=2^{-2x}\qquad\text{use}\ a^n\cdot a^m=a^{n+m}\\\\2^{1+2-3x}=2^{-2x}\\\\2^{3-3x}=2^{-2x}\iff3-3x=-2x\qquad\text{subteact 3 from both sides}\\\\-3x=-2x-3\qquad\tex\qquad\text{add}\ 2x\ \text{to both sides}\\\\-x=-3\qquad\text{change the signs}\\\\x=3[/tex]
Determine the domain of the function f (x) = 2x - 4 when the range is (0, 12, 20)
Answer:
The domain is (2,8,12)
Step-by-step explanation:
we have
[tex]f(x)=2x-4[/tex]
we know that
The range is (0,12,20)
Find the domain
1) For f(x)=0 -----> Find the value of x
substitute the value of f(x) in the equation and solve for x
[tex]0=2x-4[/tex]
[tex]2x=4[/tex]
[tex]x=2[/tex]
therefore
For f(x)=0 the domain is x=2
2) For f(x)=12 -----> Find the value of x
substitute the value of f(x) in the equation and solve for x
[tex]12=2x-4[/tex]
[tex]2x=12+4[/tex]
[tex]x=8[/tex]
therefore
For f(x)=12 the domain is x=8
3) For f(x)=20 -----> Find the value of x
substitute the value of f(x) in the equation and solve for x
[tex]20=2x-4[/tex]
[tex]2x=20+4[/tex]
[tex]x=12[/tex]
therefore
For f(x)=20 the domain is x=12
therefore
The domain is (2,8,12)
If f(x)=2x^2+3 and g(x)=x-2, what is (f+g)(2)?
[tex](f+g)(x)=2x^2+3+x-2=2x^2+x+1\\\\(f+g)(2)=2\cdot2^2+2+1=8+3=11[/tex]
Answer:
11
Step-by-step explanation:
(f+g)(2) means f(2)+g(2).
f(2) means we need to replace the x's in f(x)=2x^2+3 with 2.
This gives us f(2)=2(2)^2+3.
Let's simplify f(2)=2(4)+3=8+3=11.
g(2) means we need to replace the x's in g(x)=x-2 with 2.
This gives us g(2)=2-2
Let's simplify g(2)=0.
Now f(2)+g(2) means we just add the result of f(2) to the result of g(2).
So the problem is what is 11+0?
Answer is 11
Which of the tables represents a function? Table P Input Output 8 3 1 7 5 4 Table Q Input Output 9 3 9 5 4 2 Table R Input Output 7 2 8 6 7 3 Table S Input Output 1 7 1 5 9 2 Table P Table Q Table R Table S
Answer:
Table P represents a function
Step-by-step explanation:
* Lets explain the meaning of the function
- A function is a relation between a set of inputs and a set of outputs
in condition of each input has exactly one output
- Ex:
# The relation {(1 , 2) , (-4 , 5) , (-1 , 5)} is a function because each x in the
order pair has only one value of y
# The relation {(1 , 2) , (1 , 5) , (3 , 7)} is not a function because there is x
in the order pairs has two values of y (x = 1 has y = 2 and y = 5)
* Lets solve the problem
# Table P :
- In put : 8 , 1 , 5
- Out put : 3 , 7 , 4
∵ Each input has only one output
∴ Table P represents a function
# Table Q :
- Input : 9 , 9 , 4
- Out put : 3 , 5 , 2
∵ The input 9 has two outputs 5 and 2
∴ Table Q doesn't represent a function
# Table R :
- In put : 7 , 8 , 7
- Out put : 2 , 6 , 3
∵ The input 7 has two outputs 2 and 3
∴ Table R doesn't represent a function
# Table S :
- In put : 1 , 1 , 9
- Out put : 7 , 5 , 2
∵ The input 1 has two outputs 7 and 5
∴ Table S doesn't represent a function
* Table P represents a function
Answer:
The answer is A I just took the test
Multiple choice question?
Answer:
9* 3 ^ (x-2)
Step-by-step explanation:
g(x) = 3^x
We know a^ (b) * a^(c) = a^ (b+c)
9* 3 ^ (x+2) = 3^2 * 3 ^(x+2) = 3^(2+x+2) = 3^x+4 not equal to 3^x
3*(9^(x+2)) = 3*3^2(x+2) = 3^1 * 3^(2x+4) =3^(2x+4+1) = 3^(2x+5) not equal
9* 3 ^ (x-2) = 3^2 * 3 ^(x-2) = 3^(2+x-2) = 3^x equal to 3^x
3*(9^(x-2)) = 3*3^2(x-2) = 3^1 * 3^(2x-4) =3^(2x-4+1) = 3^(2x-3) not equal
|
Which expression is equivalent to the following complex fraction?
.
Answer:
Yes, A is correct.
An ancient artifact was recently discovered, but due to rust and corrosion, only 75 grams of the original item remained. Based on historical dates, scientists believe that this artifact was decaying at a rate of 2% each year. Although the artifact will now be preserved at a museum, scientists wonder: how much of the original artifact would there be if they had not discovered it for another 10 years?
Write an exponential function rule and solve. Round your answer to the nearest whole number (the ones place). Enter both the number and the associated units
namely, what is the leftover amount when the decay rate is 2% for an original amount of 75 grams after 10 years?
[tex]\bf \qquad \textit{Amount for Exponential Decay} \\\\ A=P(1 - r)^t\qquad \begin{cases} A=\textit{accumulated amount}\\ P=\textit{initial amount}\dotfill &75\\ r=rate\to 2\%\to \frac{2}{100}\dotfill &0.02\\ t=\textit{elapsed time}\dotfill &10\\ \end{cases} \\\\\\ A=75(1-0.02)^{10}\implies A=75(0.98)^{10}\implies A\approx 61.28\implies \stackrel{\textit{rounded up}}{A=61~grams}[/tex]
Answer with explanation:
The exponential decay function is written as :-
[tex]f(x)=A(1-r)^x[/tex], where f (x) is the amount of material left after x years , A is the initial amount of material and r is the rate of decay.
Given : The amount of original item remained now = 75 grams
The rate of decay = 2% = 0.02
Now, the amount of original artifact would there be left if they had not discovered it for another 10 years is given by :-
[tex]f(10)=75(1-0.02)^{10}[/tex]
Solving the above exponential equation , we get
[tex]=61.2804605166\approx61[/tex]
Hence only 61 grams original artifact would there be left if they had not discovered it for another 10 years .
A factory manufactures widgets based on customer orders. If a customer's order is for less than w widgets, the customer's cost per widget is d dollars. If a customer's order is for at least w widgets, the customer's cost per widget is decreased by c cents for each widget ordered over w widgets. A customer's total cost is t. Which of the following functions would best model the situation given above?
Answer:
Piecewise function model
Step-by-step explanation:
According to the given statement a factory manufactures widgets based on customer orders. If a customer's order is for less than w widgets, the customer's cost per widget is d dollars.
customer order < widgets
If a customer's order is for at least w widgets, the customer's cost per widget is decreased by c cents for each widget ordered over w widgets. A customer's total cost is t.
customer order > widgets
We can notice that we have two different conditions. In this type of question where there are different conditions for different types of domain we use piecewise function.
With different conditions, the cost is different, therefore piecewise function model would be the best option for the situation....
Write in vertex form
Answer:
p(x) = 6(x + 2)² - 3
Step-by-step explanation:
This one requires a lot of thinking because since our A is not 1 and how the quadratic equation looks, we need to think of a low number while "completing the square [½B]²". So, let us choose 2. We set it up like this:
6(x + 2)² → 6(x² + 4x + 4) → 6x² + 24x + 24
6x² + 24x + 24 - 3 → 6x² + 24x + 21 [TA DA!]
We know that our vertex formula is correct. Additionally, -h gives you the OPPOSITE terms of what they really are, and k gives you the EXACT terms of what they really are. Therefore, your vertex is [-2, -3].
I am joyous to assist you anytime.
Which of the following fractions is an improper fraction?
*2/3
*6/11
*21/25
*8/7
Answer:
8/7
Step-by-step explanation:
8/7 is an improper fraction.
8 > 7
A fraction has to have the numerator less than the denominator, in order to be a proper fraction.
In this case, 8/7 is the only fraction with a numerator more than the denominator.
Therefore, 8/7 is an improper fraction.
Answer:
8/7 is an improper fraction.
Step-by-step explanation:
An improper fraction is just a fraction where the numerator (top number) is greater than the denominator (bottom number)
2<3
6<11
21<25
8>7
Hope this helps!!!
Find the equation of quadratic function determined from the graph below?
Step-by-step explanation:
The x-intercepts are x = -1 and x = 5, so:
y = k (x + 1) (x − 5)
The vertex is (2, -3), so:
-3 = k (2 + 1) (2 − 5)
-3 = -9k
k = 1/3
y = 1/3 (x + 1) (x − 5)
Simplifying:
y = 1/3 (x² − 4x − 5)
y = 1/3 x² − 4/3 x − 5/3
f(x) = 1 / 3 x² - 4 / 3 x - 5 / 3
using the form:
f(x) = a(x - h)² + k
The vertex coordinates are 2 and -3.
h = 2
k = - 3
therefore,
f(x) = a(x - 2)² - 3
f(x) = a(x - 2)² - 3
let's use the coordinates (-1, 0) to find a. Therefore,
0 = a(-1 - 2)² - 3
0 = 9a - 3
3 = 9a
a = 3 / 9
a = 1 / 3
let's insert the value of a in the equation.
f(x) = a(x - 2)² - 3
f(x) = 1 / 3 ( x - 2)² - 3
f(x) = 1 / 3 (x - 2)(x -2) - 3
f(x) = 1 / 3 (x² - 4x + 4) - 3
f(x) = x² / 3 - 4x / 3 + 4 / 3 - 3
f(x) = 1 / 3 x² - 4 / 3 x - 5 / 3
read more here; https://brainly.com/question/10268287?referrer=searchResults